2019
DOI: 10.1016/j.clgc.2018.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Renal Cell Carcinoma: An Analysis of Clinical Characteristics

Abstract: Variations in clinical characteristics in underrepresented patients with renal cell carcinoma were investigated. This study included 294 patients and showed Hispanic and Native American patients were more likely to be diagnosed with clear-cell subtype and at a younger age than European American patients. Older Hispanic patients who spoke Spanish were more likely to have advanced stage renal cell carcinoma. Background: Racial/ethnic minority groups, including Hispanic Americans (HAs) and Native Americans (NAs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 26 publications
1
33
1
Order By: Relevance
“…A study from northern California showed that HAs were diagnosed at younger age than NHWs . Our previous study in southern Arizona also showed that HAs as well as AIs had a younger age at diagnosis . The current study provides evidence to support these findings and demonstrated major US racial/ethnic groups have an increased risk of early‐onset of RCC.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…A study from northern California showed that HAs were diagnosed at younger age than NHWs . Our previous study in southern Arizona also showed that HAs as well as AIs had a younger age at diagnosis . The current study provides evidence to support these findings and demonstrated major US racial/ethnic groups have an increased risk of early‐onset of RCC.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have also shown that papillary RCC is more common in NHBs than in NHWs, but a few studies investigated variations in RCC histologic subtypes across racial/ethnic groups. We previously found that HAs and AIs from southern Arizona had higher frequencies of ccRCC compared with NHWs . A study from Texas showed that ccRCC was very common among HAs, but in the study from northern California, the frequencies of ccRCC were similar between HAs and NHWs .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…However, whether these findings from the Caucasian population consistently can be applied in all races/ethnicity is still unknown. For example, a recent study suggested that RCC in Hispanic Americans and Native Americans have different clinical characteristics compared with European American patients [9,10]. With regard to the Asian patients, the incidence of RCC seems to be less frequent in the Asian population than Caucasian, and treatment outcomes may differ between these ethnicities suggesting that the role of prognostic factors including BMI varies between ethnicities [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…There is a preponderance of cases in males compared with females. 2 In addition, in the United States, there is a racial predilection for Hispanics and Native Americans among ccRCC cases, 3 which suggests genetic, epigenetic, and environmental factors behind the disease. In addition to sporadic ccRCC, there are familial syndromes whose symptoms include RCC.…”
mentioning
confidence: 99%